Active immunotherapy against pathogenic Cis pT231-tau suppresses neurodegeneration in traumatic brain injury mouse models. (December 2022) - Alipour, Masoume; Tebianian, Majid; Tofigh, Nahid; Taheri, Reyhaneh Sadat; Mousavi, Sayed Alireza; Naseri, Asal; Ahmadi, Amin; Munawar, Nayla; Shahpasand, Koorosh
Abstract: Traumatic brain injury (TBI), characterized by acute neurological impairment, is associated with a higher incidence of neurodegenerative diseases, particularly chronic traumatic encephalopathy (CTE), Alzheimer's disease (AD), and Parkinson's disease (PD), whose hallmarks include hyperphosphorylated tau protein. Recently, phosphorylated tau at Thr231 has been shown to exist in two distinct cis and trans conformations. Moreover, targeted elimination of cis P-tau by passive immunotherapy with an appropriate mAb that efficiently suppresses tau-mediated neurodegeneration in severe TBI mouse models has proven to be a useful tool to characterize the neurotoxic role of cis P-tau as an early driver of the tauopathy process after TBI. Here, we investigated whether active immunotherapy can develop sufficient neutralizing antibodies to specifically target and eliminate cis P-tau in the brain of TBI mouse models. First, we explored the therapeutic efficacy of two different vaccines. C57BL/6   J mice were immunized with either cis or trans P-tau conformational peptides plus adjuvant. After rmTBI in mice, we found that cis peptide administration developed a specific Ab that precisely targeted and neutralized cis P-tau, inhibited the development of neuropathology and brain dysfunction, and restored various structural and functional sequelae associated with TBI in chronic phases. In contrast, trans P-tau peptide application not only lacked neuroprotective properties, but also contributed to a number of neuropathological features, including progressive TBI-induced neuroinflammation, widespread tau-mediated neurodegeneration, worsening functional deficits, and brain atrophy. Taken together, our results suggest that active immunotherapy strategies against pathogenic cis P-tau can halt the process of tauopathy and would have profound clinical implications.